P-304 Sexual function in women with endometriosis: an online survey. (30th June 2022) - Facchin, F; Barbara, G; Buggio, L; Dridi, D; Saita, E
Abstract: Study question: What factors are associated with sexual function in women with endometriosis? Summary answer: In this study, the most important variables associated with sexual function were dyspareunia (especially deep and introital dyspareunia combined), infertility, fatigue, and psychological comorbidities. What is known already: Endometriosis is a chronic gynaecologic disease that affects women of reproductive age, with negative consequences on multiple life domains, including sexuality. Although it has been demonstrated that endometriosis-related sexual issues may negatively affect women's intimate relationships, their subjective experience remains overlooked, either in research or clinical practice. In this regard, the impact of dyspareunia (especially deep dyspareunia) has been highlighted in several studies, but the role of symptoms other than pain, such as fatigue, infertility, and psychological comorbidities, has not been yet clarified. Moreover, little is known about how women deal with dyspareunia and the quality of doctor-patient communication. Study design, size, duration: This observational study was conducted between 8 November and 21 December 2021 in collaboration with the largest Italian patient association, Associazione Progetto Endometriosi (APE [Endometriosis Project Association]). Data were collected through a self-administered online survey hosted on Qualtrics (Qualtrics Ltd.). Women were invited to participate in the study via APE's Facebook page and newsletters. The online survey was anonymous, and women were allowed to complete it only after providing their electronic consent. Participants/materials, setting, methods: Participants were 612 women (age: 36.41 ± 6.72 years) with a surgical or clinical diagnosis of endometriosis and a sexual partner. They completed the Female Sexual Function Index (FSFI), the Hospital Anxiety and Depression Scale (HADS), and the Rosenberg Self-Esteem Scale (RSES). Demographic and gynaecologic data – including endometriosis stage, type of lesions, symptoms (e.g., pelvic pain, fatigue, infertility), treatment –, and information regarding women's subjective experience of dyspareunia were collected using a researcher-made questionnaire. Main results and the role of chance: Dyspareunia was experienced by 524 (86%) women. Sexual dysfunction (FSFI total score < 26.55) was reported by 479 (78%) participants. Multiple regression analyses revealed that sexual function (FSFI total score) was associated with dyspareunia ( β  = −.108, P =  .008), infertility ( β =  −.082, P =  .040), fatigue ( β =  −.108, P =  .021), and symptoms of anxiety and depression (HADS total score; β =  −.127, P =  .021). Women with sexual dysfunction were more likely to report rectovaginal endometriotic lesions (59% vs. 47%, P =  .016) and stage 4 endometriosis (43% vs. 32%, P =  .002), to experience deep and introital dyspareunia combined (50% vs. 21%, P <  .001), with greater symptoms of anxiety and depression ( F  [2, 595] = 21.812, P <  .001, Wilk's Λ = .932, η 2 p = .068) and lower self-esteem ( t  [589] = 5.111, P <  .001). Women with dyspareunia and sexual dysfunction reported greater fear of pain and consequent inability to relax during intercourse, avoidance of sex, worries about their sexual life, sexual dissatisfaction, and feelings of guilt towards the partner ( Ps <  .001), along with poorer support and understanding from doctors ( P =  .006) than women with dyspareunia who did not report sexual dysfunction. Limitations, reasons for caution: This is one of the largest studies on sexual function in women with endometriosis. However, there are reasons for caution when interpreting our results due to the self-reported nature of all the data (including medical information) and the risk of selection bias due to our recruitment strategy. Wider implications of the findings: Our results clearly indicate that the majority of women with endometriosis experience sexual problems that are mostly (but not solely) due to dyspareunia. The assessment of sexual function should be included in routine clinical practice with these patients, also considering its association with psychological symptoms and self-esteem. Trial registration number: Not applicable